The Role of the Gut Microbiome in Pathogenesis, Biology, and Treatment of Plasma Cell Dyscrasias - Jasiński, Marcin; Biliński, Jarosław; Basak, Grzegorz W. (Frontiers in Oncology, 2021)
In response to emerging discoveries, questions are mounting as to what factors are responsible for the progression of plasma cell dyscrasias and what determines responsiveness to treatment in individual patients. Recent findings have shown close interaction between the gut microbiota and multiple myeloma cells. For instance, that malignant cells shape the composition of the gut microbiota. We discuss the role of the gut microbiota in (i) the development and progression of plasma cell dyscrasias, and (ii) the response to treatment of multiple myeloma and highlight faecal microbiota transplantation as a procedure that could modify the risk of progression or sensitize refractory malignancy to immunotherapy.